Morphology and phylogenetic position of a trebouxiophycean green alga (Chlorophyta) growing on the rubber tree, Hevea brasiliensis, with the description of a new genus and species - Zhang, Jiaming; Huß, Volker; Sun, Xuepiao; Chang, Kaijun; Pang, Daobiao (European Journal of Phycology, 2008)
A novel unicellular Chlorella-like green alga was isolated from the rubber tree (Hevea brasiliensis). The cultured cells were described by light and electron microscopy. Most adult cells were spherical with a single cup-shaped parietal chloroplast, although a few cells contained 2 to 4 chloroplasts. Chloroplasts contained many small pyrenoids with pyrenoglobuli around the multi-oriented tube-like thylakoids in the pyrenoid matrix. Most sporangia contained 2 or 4 autospores with a spindle-shaped chloroplast. Phylogenetic analyses inferred from both chloroplast-encoded 16S and nuclear-encoded 18S rDNA sequences placed our isolate in the 'Chlorella' luteoviridis clade within the class Trebouxiophyceae. There are two group I introns in the 18S rDNA, structurally similar to 'Chlorella' trebouxioides, which also has two introns at the same positions. The exon sequence revealed highest similarities of 93-95% compared with 'C.' luteoviridis, 'Chlorella' saccharophila, and 'C.' trebouxioides. The chloroplast 16S rDNA has a unique 46-bp insertion in helix P21-1, which can be folded into a double hairpin structure. Blast searches resulted in best hits of 96% similarity to 'C.' luteoviridis (CCAP-211/3), and of 91% to 'C.' saccharophila (SAG 211-1d). Based on morphological features and phylogenetic position, a new genus Heveochlorella gen. nov. with the type species H. hainangensis sp. nov. is proposed. © 2008 British Phycological Society.
Keywords: Chlorella; Chlorophyta; Chloroplast; Double hairpin element; Phylogeny; Pyrenoid; Taxonomy; Trebouxiophyceae